2016
DOI: 10.3390/ijms17111799
|View full text |Cite
|
Sign up to set email alerts
|

miR-92a-3p Exerts Various Effects in Glioma and Glioma Stem-Like Cells Specifically Targeting CDH1/β-Catenin and Notch-1/Akt Signaling Pathways

Abstract: MicroRNAs (miRNAs) are implicated in the regulation of tumor progression and stemness of cancer stem-like cells. Recently, miR-92a-3p was reported to be up-regulated in human glioma samples. Nevertheless, the precise role of miR-92a-3p in glioma cells and glioma stem-like cells (GSCs) has not been fully elucidated. It is necessary to clarify the function of miR-92a-3p in glioma and GSCs to develop novel therapeutic approaches for glioma patients. In the present study, we applied methyl-thiazolyl-tetrazolium (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…In a recent study, Song, et al reported that miR-92a-3p can target Notch1 to inhibit glioma. 12 In this study, we also observed the downregulation of Notch1 in EC cells after miR-92a-3p overexpression. Therefore, miR-92a-3p may also target Notch1 in EC.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In a recent study, Song, et al reported that miR-92a-3p can target Notch1 to inhibit glioma. 12 In this study, we also observed the downregulation of Notch1 in EC cells after miR-92a-3p overexpression. Therefore, miR-92a-3p may also target Notch1 in EC.…”
Section: Discussionsupporting
confidence: 63%
“…10 In cancer biology, Notch signaling is dysregulated and plays varied roles in different types of cancers by regulating cancer cell behaviors. 11 In a recent study, Song, et al reported that miR-92a-3p can target Notch1 to participate in glioma, 12 while the interaction between miR-92a-3p and Notch1 in other malignancies remains elusive. LncRNA DCST1-AS1 is recently characterized by oncogenic lncRNA in liver cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, prediction websites revealed that there were potential binding sites among circ_0002232, miR-92a-3p, and PTEN. MiR-92a-3p expression has been revealed to be up-regulated in several solid cancers including breast cancer and brain glioma 30,31 . According to our experiment, miR-92a-3p expression of AML patients was obviously up-regulated compared with controls and was negatively correlated with the expression of circ_0002232.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers found a similar increase in expression in gliomas and suggested that it can be a marker of glioma (Blümcke et al, 2001). Some researchers argue that MAP2 plays a dual role in the progression of cancer, which was studied in non-glioma tumors (Song et al, 2016). However, some authors assert that MAP2 may even be a positive marker of glioma, as shown in (Yi et al, 2018).…”
Section: Fig 4 Normalized Expression Of Target Genes In Human Gliobmentioning
confidence: 98%